Characteristics and in-hospital mortality of patients with myocardial infarction in the absence of obstructive coronary artery disease in super-aging society. (15th February 2020) - Ishii, Masanobu; Kaikita, Koichi; Sakamoto, Kenji; Seki, Tomotsugu; Kawakami, Koji; Nakai, Michikazu; Sumita, Yoko; Nishimura, Kunihiro; Miyamoto, Yoshihiro; Noguchi, Teruo; Yasuda, Satoshi; Tsutsui, Hiroyuki; et al.
Abstract: Background: Myocardial infarction with nonobstructive coronary arteries (MINOCA) is a common presentation of acute myocardial infarction (AMI) and has a better prognosis. However, there were few reports on large-scale, high aged population. The aim of this study was to determine the differences in the clinical characteristics and short-term prognosis between MINOCA and myocardial infarction with obstructive coronary artery disease (MI-CAD) using a nationwide administrative database in the super-aging society, Japan. Methods: This was an observational study using data of 137, 678 AMI patients who underwent angiography between April 2012 through March 2016. Using the international classification of diseases 10th revision, AMI patients were divided into two groups based on the presence or absence of revascularization and coronary atherosclerosis, identifying 123, 633 MI-CAD and 14, 045 working diagnosis of MINOCA patients. The true MINOCA (n = 13, 022) was defined as the MINOCA excluding non-ischemic causes. We assessed in-hospital mortality within 30 days. Results: Both MINOCA groups were typically found in non-obese, non-smoker young females, with a low grade on Killip classification, and non-low ADL status. Compared to MI-CAD, chronic pulmonary diseases, peripheral vascular diseases, liver diseases, renal diseases, and cerebrovascular diseases were more common, whereas diabetes was less common in the MINOCA groups. In-hospital mortality within 30 days was higher in both MINOCA groups than in MI-CAD. Multivariate frailty model identified both MINOCA groups as an independent risk factor for in-hospital mortality. Conclusions: Our large-population study demonstrated that MINOCA was associated with a high risk of in-hospital mortality compared with MI-CAD in the super-aging society. Highlights: This study showed the characteristics of MINOCA in the super-aged society. MINOCA was associated with a higher risk for in-hospital mortality. The prognosis of MINOCA was heterogeneous due to the diversity of the causes.